Role of the peripheral chemoreflex in the early stages of ventilatory acclimatization to altitude. - Robbins, P (2007)
This review of ventilatory acclimatization to altitude/hypoxia (VAH) emphasizes the widely differing timescales that VAH is considered to encompass. The review concludes: (1) that early (24-48h) VAH is unlikely to arise as a reaction to the respiratory alkalosis that is normally associated with exposure to hypoxia; (2) that changes in peripheral chemoreflex function may be sufficiently rapid to explain early VAH; (3) that alterations in gene expression induced by hypoxia through the hypoxia-inducible factor (HIF) signalling pathway may underlie a major component of VAH; and (4) that compensatory adjustments to acid-base balance in response to the initial respiratory alkalosis may have more significance for the slower changes observed later in VAH.